Effect of passive pre-chamber orifice diameter on the methane combustion process in an optically accessible SI engine. (1st June 2023) - Antolini, Jácson; Sementa, Paolo; Tornatore, Cinzia; Catapano, Francesco; Vaglieco, Bianca Maria; Desantes, José M.; López, J. Javier
Highlights: The effect of the orifice diameter of a novel passive pre-chamber (PC) on the combustion process was assessed. The PC with a 1.2 mm orifice diameter showed the fastest combustion, followed by 1.5 and lastly 1.0 mm. The SI engine equipped with the PC showed a higher equivalent flame front velocity than the typical operation. Abstract: Due to its potential to extend the lean limit or overcome knock-limited conditions on spark-ignited (SI) engines, the pre-chamber spark-ignition (PCSI) concept has gained attention as an efficient alternative to the conventional ignition architecture. Nevertheless, especially in engine-like conditions, the effect of the main geometrical parameters on combustion development is still not fully understood and might be a hindrance to the use of this technology. In this sense, the current study aims to evaluate the effect of the orifice diameter on the jet characteristics and main chamber combustion of a novel passive pre-chamber in an optically accessible single-cylinder SI engine, as well as to compare the PCSI with the typical SI ignition method. High-speed broadband chemiluminescence imaging was used to track the jet penetration and flame front propagation of three mixture compositions at various spark timings (ST). Additionally, based on the in-cylinder pressure, a heat-released analysis was performed to assess the overall combustion process. When compared with the typical SI, the pre-chamber concept presented a higher equivalent flame front velocity, which is also corroborated by the higher in-cylinder pressure rise rate and rate of heat released. For all mixtures tested, the 1.2 mm orifice diameter PC presented the shortest flame development angle (crank angle interval between ST and 10 % of mass fraction burned in the MC), followed by 1.5 and lastly 1.0 mm. When comparing different STs, the shortest flame development angle occurred at MBT condition. Despite the highest flame development angle, the PC 1.0 mm case presented the lowest main chamber combustion duration (CA10-90), which increases as the orifice diameter is increased.